Improving office workers’ mental health and cognition: a 3-arm cluster randomized controlled trial targeting physical activity and sedentary behavior in multi-component interventions - Nooijen, Carla F. J. (BMC Public Health, 2019)
BACKGROUND: Physically inactive and sedentary lifestyles are negatively related to both mental health and cognition. For office-workers, who spend two-thirds of their workday sitting, it is important to improve these lifestyles. The aim of this study is to assess the effectiveness of multi-component interventions, incorporating individual, environmental and organizational changes, to increase physical activity or reduce sedentary behavior among office-workers in order to improve mental health and cognition. METHODS: a 3-arm, clustered randomized controlled trial (RCT) with waiting list control group amongst adult office-workers of two large Swedish companies. Cluster teams will be randomized into 6-month interventions or to a passive waiting list control group which will receive the allocated intervention with a 6-month delay. Two multicomponent interventions will be studied of which one focuses on improving physical activity and the other on reducing sedentary behavior. Both interventions include 5 sessions of motivational counselling. In the physical activity intervention persons also get access to a gym and team leaders will organize lunch walks and encourage to exercise. In the sedentary behavior intervention standing- and walking meetings will be implemented and team leaders will encourage to reduce sitting. The recruitment target is 110 office-workers per arm (330 in total). Measurements will be repeated every 6 months for a total intended duration of 24 months. Proximal main outcomes are physical activity measured with accelerometers and sedentary behavior with inclinometers. Distal outcomes are self-reported mental health and a cognition test battery. Additional outcomes will include cardiovascular fitness, body composition, sleep, self-reported physical activity and sedentary behavior, other health habits, physical health, and working mechanisms from blood samples and questionnaires. DISCUSSION: This cluster RCT will contribute to the currently available evidence by comparing the effectiveness of multi-component interventions targeting physical activity or sedentary behavior with the end goal of improving mental health and cognition. This study is strong in its cluster randomized design, numerous objective outcome measures and long-term follow-up. The exact content of the interventions has been defined by combining theory with results from a larger research project as well as having a continuous dialogue with the involved companies. TRIAL REGISTRATION: ISRCTN92968402. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12889-019-6589-4) contains supplementary material, which is available to authorized users.